The American Association of Endocrine Surgeons Guidelines for the Definitive Surgical Management of Thyroid Disease in Adults. Issue 3 (March 2020) - Patel, Kepal N.; Yip, Linwah; Lubitz, Carrie C.; Grubbs, Elizabeth G.; Miller, Barbra S.; Shen, Wen; Angelos, Peter; Chen, Herbert; Doherty, Gerard M.; Fahey, Thomas J.; Kebebew, Electron; Livolsi, Virginia A.; et al.
Abstract : Objective: To develop evidence-based recommendations for safe, effective, and appropriate thyroidectomy. Background: Surgical management of thyroid disease has evolved considerably over several decades leading to variability in rendered care. Over 100, 000 thyroid operations are performed annually in the US. Methods: The medical literature from 1/1/1985 to 11/9/2018 was reviewed by a panel of 19 experts in thyroid disorders representing multiple disciplines. The authors used the best available evidence to construct surgical management recommendations. Levels of evidence were determined using the American College of Physicians grading system, and management recommendations were discussed to consensus. Members of the American Association of Endocrine Surgeons reviewed and commented on preliminary drafts of the content. Results: These clinical guidelines analyze the indications for thyroidectomy as well as its definitions, technique, morbidity, and outcomes. Specific topics include Pathogenesis and Epidemiology, Initial Evaluation, Imaging, Fine Needle Aspiration Biopsy Diagnosis, Molecular Testing, Indications, Extent and Outcomes of Surgery, Preoperative Care, Initial Thyroidectomy, Perioperative Tissue Diagnosis, Nodal Dissection, Concurrent Parathyroidectomy, Hyperthyroid Conditions, Goiter, Adjuncts and Approaches to Thyroidectomy, Laryngology, Familial Thyroid Cancer, Postoperative Care and Complications, Cancer Management, and Reoperation. Conclusions: Evidence-based guidelines were created to assist clinicians in the optimal surgical management of thyroid disease.